Edukasi Produk Jajanan yang Dapat Merusak Gigi pada Anak Usia Sekolah di SD Islam Kreatif The Naff Kediri - Lukis, Prima Agusti; Hariyani; Fitria, Faizatul; Gustina, Mara; Afnani, Fawait (Journal of Science and Social Development, 2024)
Consumption of sugary, acidic, and refined carbohydrate-rich foods and drinks is a major cause of tooth decay, increasing dental caries among children. This community service program aims to raise awareness, especially among school-aged kids, about the dangers of such snacks. Through an educational approach, leaflets about harmful snacks like candy, soda, and other sugary treats were distributed. Pre- and post-intervention questionnaires measured participants' understanding. Initially, most children were unaware of the dental health risks of sugary snacks. After the intervention, knowledge about toothdecay-causing snacks increased by 95%, alongside a better grasp of healthy habits to maintain dental health. Early education on proper food choices and dental care can reduce dental caries prevalence among children. This program successfully boosted dental health awareness in the elementary school environment.